Drug utilisation evaluation in patients with osteoarthritis in tertiary care hospital - Rasheed, Abdul; Muneebullah, Mohammed; Maqsood, Mohammed; Khan, Arbaz Ahmed; Ahmed, Mohamed (International Journal of Basic & Clinical Pharmacology, 2022)
Background: The principle aim of our study is to assess the prescribing pattern of drugs used in treatment of osteoarthritis patients. Methods: A prospective and empirical study was carried out at department of orthopaedics-Shadan teaching and general hospital, for 6 months. Results: During the study period, a total 120 patients were enrolled, of which 57% were females, 43% were males and common age group was ≥60 years. It was found that 56% of OA patient have history of trauma and 62% of obese individual contribute to occurrence of OA. It was found that subjects developed comorbidities like CV disorders which is 36%. It was found that 63% have OA for a duration of >2 years, 56% had no knowledge about their medications, 59% have co-morbidity, 61% have treatment complexity. NSAID’s, calcium, vitamin D3, glucosamine and chondroitin sulphate were the most frequently prescribed drugs in OA accounting for 50%. It was reported that 55% were adherent to OA medication, adherence to physical activity was 64%, adherence to weight loss was 62%. Conclusions: Our study manifest that majority of the patients had duration of >2 years of OA. The reasons for the uncontrolled pain was due to absence of awareness about osteoarthritis-related difficulties, drugs, low calcium diet, increased stress, obesity, and advanced age. Continuous health education, patient counselling, information about medication adherence and satisfaction at follow-ups is essential to avoid the problems.